2012
DOI: 10.3390/app2040682
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated and Non-Fluorinated Electro-Optic Copolymers: Determination of the Time and Temperature Stability of the Induced Electro-Optic Coefficient

Abstract: Abstract:Organic fluorinated materials demonstrate their excellent electro-optic properties and versatility for technological applications. The partial substitution of hydrogen with fluorine in carbon-halides bounds allows the reduction of absorption losses at the telecommunication wavelengths. In these interesting compounds, the electro-optic coefficient was typically induced by a poling procedure. The magnitude and the time stability of the coefficient is an important issue to be investigated in order to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…The quadratic EO effect is significantly weaker compared to the linear EO effects but it does not require the lack of centrosymmetry of the system. Moreover, it was demonstrated that the quadratic EO effect is very attractive due to its inherent long-term and thermal stability compared to the linear EO effect in polymers [9], [10] and its potential high bandwidth [11]. One major advantage of third-order nonlinear optical polymers is that they exhibit the quadratic EO effect as well as the all-optical Kerr-effect at the same time, leading to completely new device concepts; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The quadratic EO effect is significantly weaker compared to the linear EO effects but it does not require the lack of centrosymmetry of the system. Moreover, it was demonstrated that the quadratic EO effect is very attractive due to its inherent long-term and thermal stability compared to the linear EO effect in polymers [9], [10] and its potential high bandwidth [11]. One major advantage of third-order nonlinear optical polymers is that they exhibit the quadratic EO effect as well as the all-optical Kerr-effect at the same time, leading to completely new device concepts; e.g.…”
Section: Introductionmentioning
confidence: 99%